Performance Appraisal in Greek Public Sector - Amygdalos, Charalampos; Bara, Nikoleta; Moisiadis, Georgios (Procedia, social and behavioral sciences, 2014)
The basic element of the survey is the investigation of the Greek public sector and in particular the way in which the system evaluates the performance of undertaken task. In this article, we examine the relationship between the variables (gender, age) and the variables (objective/subjective potential in appraisal and general attribute of the subjects for appraisal to the appraisal system). As far as the gender is concerned (male, female), it is obvious that this variable can have different influence on the attribute of those asked and the same happens with age, which is of equal importance.